Hybrid nanofluid flow past a biaxial stretching/shrinking permeable surface with radiation effect: Stability analysis and heat transfer optimization - Yahaya, Rusya Iryanti; Mustafa, Mohd Shafie; Md Arifin, Norihan; Pop, Ioan; Md Ali, Fadzilah; Mohamed Isa, Siti Suzilliana Putri (Elsevier BV, 2023)
Fluid flow over a biaxial stretching/shrinking surface may arise in fiber production and wrapping processes. The current study considered the three-dimensional flow of a hybrid nanofluid past a biaxial stretching/shrinking sheet with thermal radiation and suction. This flow problem is translated into nonlinear partial differential equations and boundary conditions. After similarity transformations, the numerical computations are conducted using the bvp4c solver. The calculation yielded dual solutions that prompted a stability analysis, demonstrating that only the first solution is stable and significant. Cu-Al2O3/H2O hybrid nanofluid produced the highest temperature profile compared to Cu/H2O and Al2O3/H2O nanofluids. As observed from this study, a further increase in the temperature profile of the hybrid nanofluid can be achieved by enhancing the shrinking and radiation parameters. Meanwhile, the magnitude of the skin friction coefficient and heat transfer rate rises with the suction parameter. At the same time, the suction parameter reduces the thickness of the momentum and thermal boundary layers. Then, response surface methodology (RSM) is used to develop a correlation between the response, Nusselt number, Re− 1/2 x Nux, and governing parameters of the problem. The RSM suggested that the suction parameter positively affects the heat transfer rate. However, the opposite behavior is observed for the nanoparticle volume fraction of Cu and Al2O3. The heat transfer rate is estimated to be optimized at 6.02216 when ϕCu = ϕAl2O3 = 0.02 and S = 3.0.